Global Monitoring Report 2011 : Improving the Odds of Achieving the MDGs - World Bank (World Bank, 2012)
This report has been prepared jointly by the staffs of the World Bank and the International Monetary Fund (IMF). This year we are facing historic development challenges from natural disasters, to food and fuel price spikes, and profound change in the Middle East. Despite high beverage growth in the developing world, it is crucial to provide opportunities to those that are being left behind. Wealthier economies are experiencing slower growth but development assistance needs remain high. In our interconnected world, sustainable recovery means supporting inclusive growth. Only four years remain until the 2015 deadline for reaching the Millennium Development Goals (MDGs). The global monitoring report 2011: improving the odds of achieving the MDGs heterogeneity, gaps, and challenges underlines the urgency of helping countries that are behind on meeting key targets for extreme poverty, hunger, disease, and child and maternal mortality. The report lays out the challenges that remain; analyzes efforts to improve human development; and assesses the role of growth, policy reforms, trade, and donor policies in meeting the MDGs. The findings from this year's report offer reason for both hope and concern. The MDGs were designed to provide a framework for the entire international community to work together toward a common end: making sure that human development reaches everyone, everywhere. If these goals are achieved, billions more people will have the opportunity to benefit from the global economy.